Caries prevalence and DMF-T index of Papuanâs students with Betel chewing habit - Tebai, Yohanes; Sukartini, Endang; Hayati, Ayu Trisna (Padjadjaran Journal of Dentistry, 2009)
The purpose of the research is to find the extent of caries prevalence and DMF-T index in Papuanâs students with betel chewing habit in Cilaki Dormitory Bandung, 2007. Betel chewing habit is a chewing action of Areca nut (Areca Catechu Linn), Betel leaves (Piper Betel Folia), Betel fruit (Piper Betle Linn), lime talk (Calcium Hydroxide), and after chew to spent out of the mouth. The research is a descriptive research using the survey technique. Research samples are determined by purposive sampling, and a number of 80 samples are collected, consisting of Papuanâs student with betel chewing habit in Bandung between 18-to-30 years of age. Research results indicated that caries prevalence is 98.75% with a DMF-T index of 5.46. The conclusion of the reseach is that the caries prevalence and the DMF-T in Papuanâs student with betel chewing habit in Cilaki Papuanâs Student Dormitory Bandung, 2007, is in the high category.